Taxonomic review of the genus Herpystis Meyrick, 1911 (Lepidoptera, Tortricidae) from China, with descriptions of four new species - Bai, Xia; Li, Houhun (Zootaxa, 2019)
Five species of Herpystis Meyrick, 1911 are reported from China, four of which species are described as new: H. densisetosa, sp. nov.; H. medispinata, sp. nov.; H. arcisaccula, sp. nov.; and H. orthocera, sp. nov. Herpystis mica Kuznetzov, 1988 is newly recorded in China. Photographs of adults and genitalia are provided, along with a key to the Chinese species.